Implementing quality indicators for diabetes and hypertension in family medicine in Slovenia - Klemenc-Ketiš Zalika; Švab Igor; Poplas Susič Antonija (Sciendo, 2017)
A new form of family practices was introduced in 2011 through a pilot project introducing nurse practitioners as members of team and determining a set of quality indicators. The aim of this article was to assess the quality of diabetes and hypertension management.